2016
DOI: 10.21037/jtd.2016.10.32
|View full text |Cite
|
Sign up to set email alerts
|

Coronary bifurcation lesions: is less more?

Abstract: Coronary bifurcation lesions are frequent in everyday practise and account for up to 20% of all percutaneous coronary interventions (PCI) (1). The treatment of bifurcation lesions with drug-eluting stents (DES), especially when a double stent technique is used, remains challenging and is associated with a lower procedural success rate and a higher rate of long-term adverse cardiac events such as stent restenosis and thrombosis compared to non-bifurcation PCI (2). The question relating to a one or two stent str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…By design, dedicated bifurcation devices offer solutions against the limitations of tubular stents by conforming to bifurcation anatomy and avoiding stent deformation and overlap. Theoretically, they represent a valid alternative to the ongoing controversy of single versus double tubular stent strategies to be used in a bifurcation scenario [15][16][17]. However, implantation of dedicated bifurcation stents is technically demanding and the learning curve relating to patient/lesion selection and technical implementation, both hamper breakthrough of the technique in daily practice as well as evaluation of its true value.…”
Section: Discussionmentioning
confidence: 99%
“…By design, dedicated bifurcation devices offer solutions against the limitations of tubular stents by conforming to bifurcation anatomy and avoiding stent deformation and overlap. Theoretically, they represent a valid alternative to the ongoing controversy of single versus double tubular stent strategies to be used in a bifurcation scenario [15][16][17]. However, implantation of dedicated bifurcation stents is technically demanding and the learning curve relating to patient/lesion selection and technical implementation, both hamper breakthrough of the technique in daily practice as well as evaluation of its true value.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary bifurcations are frequent and account for approximately 20% of all percutaneous coronary interventions [1]. Nonetheless,they represent one of the remaining challenges in interventional cardiology and the uniform strategy is still the subject of substantial debate in terms of a lower procedural success rate,a higher risk of procedural complications, and increasing rates of long-term adverse cardiac events [2].…”
Section: Introductionmentioning
confidence: 99%
“… 7 The anatomy and the severity of the lesion, are important factors to take into account when deciding whether to use a provisional or a complex strategy. 8 A 2015 clinical trial found that patients undergoing PCI with true bifurcation lesions—defined as lesions affecting both the MV vessel and the ostium of the SB, Medina classification 1, 1, 1; 1, 0, 1; or 0, 1, 1, also involving a SB reference vessel diameter (RVD) of ≥ 2.3 mm—had worse clinical outcomes than patients without true bifurcation lesions. 2 , 9 The authors strongly recommend differentiating the two types of bifurcation lesions in future studies.…”
Section: Introductionmentioning
confidence: 99%